INTEGRASI COMMUNITY-BASED TOURISM DAN KONSERVASI LINGKUNGAN DALAM PERENCANAAN PARIWISATA BERKELANJUTAN MELALUI PENDEKATANSITUATION, QUESTION, LITERATURE, RECOMMENDATION (SQLR) - Pahima Pahima; Imaduddin Al Azzam (Journal Economics Technology And Entrepreneur, 2025)
The development of sustainable tourism faces several significant challenges, including ecological degradation, unequal distribution of economic benefits, and the limited integration of local communities in planning processes. Environmental conservation serves as a fundamental pillar in ensuring the ecological sustainability of tourism destinations, while Community-Based Tourism (CBT) emerges as an approach that emphasizes the active participation of local communities in tourism development. Nevertheless, the implementation of CBT in sustainable tourism planning continues to reveal conceptual and practical gaps, particularly in relation to limited community capacity, unequal access to resources, and weak coordination among stakeholders. This study aims to analyze the integration of CBT and environmental conservation in sustainable tourism planning using the Situation, Question, Literature, and Recommendation (SQLR) approach. Specifically, the study seeks to identify the contextual conditions and implementation issues of conservation-based CBT, formulate research questions that highlight existing conceptual and practical gaps, analyze the literature to examine integration models that have been developed, and provide recommendations for future theoretical and research directions. The findings indicate that the integration of CBT and environmental conservation tends to be successful when local communities are not merely beneficiaries of economic gains but also act as key decision-makers, resource managers, and environmental monitors. Based on the synthesis of these findings, this study proposes a community-led conservation tourism framework (CLCTF) as a conceptual model that positions local communities as the primary drivers of conservation and tourism development. This framework underscores the importance of integrating social, ecological, economic, and institutional dimensions in sustainable tourism planning.